Life Long Education dalam Perspektif Al-Quran dan Hadis - Dian Astutik; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This researcher on long life education from the perspective of the Koran and Hadith aims to explore how to learn throughout life / long life education according to the Koran and Hadith. As well as analyzing how the concept of learning is reflected in the daily life practices of Muslims. This researcher used a qualitative type of approach with a descriptive type and the data collection process was carried out through observation, interviews and documentation. The data analysis used is data triangulation by displaying data, data reduction, data presentation, and verification. This researcher formulated two problem formulations, namely: (1) What is the urgency of longevity education according to the Koran and Hadith (2) What is the concept of Longevity Education in the Koran and Hadith. The results of this research show that (1) Learning is part of a natural human need (2) Learning is a process towards changing behavior for the better, either through reading, observation, research, reflection and direct experience (3) Al-Qur'an believers are instructed to study continuously, so that they can develop to reach perfection as servants of Allah and His caliphs (4) The object of reading/learning includes all phenomena of the universe, humans, history, signs of the times, etc. (5) Learning is a way to achieve success and happiness.